The contribution of working environment, workload, and organization culture toward work stress in UPEN Melaka and TAPEM / Assila Mohd Rosli and Jannati ‘Izzati Yahliman - Mohd Rosli, Assila; Yahliman, Jannati ‘Izzati (Faculty of Business and Management, 2014)
Work Stress has become a common problem faced by working people, due to various factors such as working environment, job characteristics, employer leadership style, workloads and others. This research endeavour relationship between working environment, workloads, and organizational culture towards employee work stress. Researcher has distributed set of questionnaire to 73 respondents at all departments in UPEN Melaka and TAPEM. In finding analysis the results is obtained from Pearson Correlation that showed the relationship between independent and dependent variable. Therefore according to Pearson Correlation analysis, only workloads have positive relationship with employee work stress. Meanwhile, others independent variables are not related to employee work stress. According to the finding result, the researcher has suggested some recommendation to solve the problem that caused stressor and reduce number of employee workstress in a future.